Information Technology Governance Audit Using COBIT 5 of DSS Domain (Deliver, Service, And Support) Framework at Malikussaleh University Lhokseumawe - Safwandi, Safwandi; Muthmainnah, Muthmainnah; Jannah, Misbahul; Lubis, Hamdi Akmal (Institute for Research and Community Service, Universitas Malikussaleh, Indonesia, 2022)
Information technology is very important for companies or institutions to support the achievement of the company's strategic plans to achieve their goals, vision, and mission. Nowadays, an institution can improve the performance of information technology that goes hand in hand with the development of information technology to produce better technology by auditing information technology governance in the company. The purpose of this study is to analyze IT governance using the COBIT 5 framework in the DSS domain at Malikussaleh University Lhokseumawe. COBIT 5 provides a comprehensive framework that helps companies achieve their goals in corporate governance and IT governance. The framework helps companies create optimum value from IT by maintaining a balance between realizing benefits and optimizing risk and resource usage levels. By conducting an audit of information technology governance in the company, the company can find out whether the information technology that has been operating is in accordance with the business processes and company objectives and convey accurately based on the IT strategy. The results of the information technology governance audit based on COBIT 5 in the DSS Domain, on average are at 2.2 (Manage process) to 2.6 (Established Process).